The effect of the pair-comparative competition method on developing some motor skills and accuracy in fencing for students - Tahseen, L.Dr.Tahseen Hosni; Shehab, Asst.L.Badraa Malek (Sulaimani Journal for Humanities, 2026)
The methods used in teaching the prescribed subjects do not focus on activating the role of the university student throughout their studies and empowering them to proactively address and overcome the educational challenges they encounter in their professional lives. This also hinders their academic and skill development in subjects such as fencing. Based on their teaching experience, the researchers observed a clear weakness in students' motor skills and thrusting accuracy. Furthermore, the extensive content of the third-year fencing curriculum, the limited time allotted, and the students' weak technical performance in this sport have highlighted the current problem. To address this, they sought a more effective teaching method to facilitate faster and more efficient learning than traditional approaches. The researchers believe that competitive learning activities are as effective in developing motor skills as any other method. Competition can be effective if used correctly. A teacher's choice of a competitive learning method leads to improved educational attainment on the one hand, and motivates students to redouble their efforts to compete with themselves or their peers on the other. Therefore, the researchers decided to undertake this study to determine the effect of the comparative competition method on developing certain motor skills and foil throwing accuracy in fencing students. The research aimed to: 1- Develop an educational program using the comparative pairs competition method to improve certain motor skills and foil throwing accuracy in fencing. 2- Determine the effect of the comparative pairs competition method on developing certain motor skills and foil throwing accuracy in fencing students. The most important conclusions were: 1- There is a clear improvement in the level of motor skills and throwing accuracy in the experimental group. 2- There is a clear improvement in the level of motor skills and throwing accuracy in the control group. 3- The proposed exercises have a greater effect on developing motor skills and throwing accuracy in the experimental group.
Keywords: The style of the paired; comparative competition; motor skills accuracy of thrusting with the foil weapon